2015
DOI: 10.1111/and.12481
|View full text |Cite
|
Sign up to set email alerts
|

Additional deleterious effects of alcohol consumption on sperm parameters and DNA integrity in diabetic mice

Abstract: The aim of this study was to survey the impact of alcohol consumption on sperm parameters and DNA integrity in experimentally induced diabetic mice. A total of 32 adult male mice were divided into four groups: mice of group 1 served as control fed on basal diet, group 2 received streptozotocin (STZ) (200 mg kg(-1) , single dose, intraperitoneal) and basal diet, group 3 received alcohol (10 mg kg(-1) , water soluble) and basal diet, and group 4 received STZ and alcohol for 35 days. The cauda epididymidis of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 17 publications
3
23
1
1
Order By: Relevance
“…Thereafter, it was stained for 10 min in freshly prepared acridine orange (0.19 mg/mL in Mcllvain phosphate–citrate buffer, pH 4.0). The smear was then examined under a fluorescent microscope (Olympus BX41) with a 460‐nm filter (Pourentezari et al ., ). For each rat, two slides were stained, and the number of spermatozoa with fragmented nDNA (orange–red fluorescence) was counted in 100 spermatozoa/field.…”
Section: Methodsmentioning
confidence: 97%
“…Thereafter, it was stained for 10 min in freshly prepared acridine orange (0.19 mg/mL in Mcllvain phosphate–citrate buffer, pH 4.0). The smear was then examined under a fluorescent microscope (Olympus BX41) with a 460‐nm filter (Pourentezari et al ., ). For each rat, two slides were stained, and the number of spermatozoa with fragmented nDNA (orange–red fluorescence) was counted in 100 spermatozoa/field.…”
Section: Methodsmentioning
confidence: 97%
“…Diabetes mellitus (DM) DM is one of the most common diseases that threats human health in the modern world ( 17 ). Its effects on human health are mostly due to the hyperglycaemic and hypoinsulinemic states caused by the disease, usually affecting neurological, endocrinological, and reproductive functions ( 18 - 20 ). DM has been related to the sexual dysfunction, both in men and women.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the concentration of seminal insulin is higher than that in the serum. Numerous studies have demonstrated a marked reduction in sperm quality in diabetic male human and animals ( 20 , 24 ). Mangoli et al showed that DM had negative effects on the sperm parameters and chromatin features in mice ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from alcohol, chronic diseases like diabetes has been associated with infertility too. Another experimental study that involved ethanol consumption in diabetes animal model has been established (Pourentezari et al, 2016). This study used male mice with streptozotocin (200 mg/kg, single dose, intraperitoneal) for diabetes induction.…”
Section: Preclinical Evidencementioning
confidence: 99%